Long Term Evaluation of Post-Partum Intrauterine Device (PPIUD) In Terms of Safety and Efficacy (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Objectives: The purpose of this study was to evaluate the long term safety and efficacy of postpartum IUCD at a tertiary level hospital.Materials & Methods: This cross sectional study was carried out in Shaheed Suhrawardy Medical College & Hospital (ShSMCH) from March 2019 to December 2019. International Federation of Gynecology and Obstetrics (FIGO) in collaboration with Obstetrical and Gynecological Society of Bangladesh (OGSB) have been launched a project in Bangladesh to foster family planning activities by postpartum IUCD insertion since July 2015 in this hospital. All patients who were inserted PPIUD following delivery under FIGO- PPIUD project since 1st January 2017 to 31st December, 2017 were included in this study. Phone number of those PPIUD inserted women were collected from the register book. Clients were evaluated after 2 years of insertion. The outcome measures analyzed were safety measures – menstrual irregularities, vaginal discharge, pelvic infection, perforation and efficacy measures – continuation, removal, expulsion and failure rate.Result: Total number of patients delivered at ShSMCH in 2017 were 2,593. Out of them deliveries, 329 (12.70%) were introduced PPIUD. Among 329 PPIUD users, after about 2 years, 175 (53.20%) could be traced for follow up and rests couldn’t be reached by repeated attempts on phone call. After telephone call they attended our hospital and thorough interview and examination was done. All the informations were collected in a predesigned data collection sheet. Among 175 study population, 25 (14.28%) IUCD introduction were following vaginal delivery and 150 (85.71%) were during cesarean section operation. Those who are continuing PPIUD, 100 (82.0%) had no complications and few, 22 (18.0%) had some minor complaints for which they received treatment. The most common adverse event was the menstrual irregularities. There was no case of perforation. By the end of 2 years, out of 175 PPIUD inserted clients, missing string was found in 85 (69.7%) cases, continuation rate of PPIUD was 122 (69.7 %), spontaneous expulsion was 10 (5.7%), removal was 43 (24.6%) and failure rate was 3 (1.7%).Conclusion: PPIUCD is a safe, effective and convenient method of contraception and should be encouraged after both vaginal and Cesarean deliveries.Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 81-89